Research progress of solid waste resource utilization backfill mining for Jinchuan Nickel Mine, China - Hui, Cao; Aiai, Wang; Lianku, Xie; Xi-Zhi, Zhang; Yong-Ding, Wang; Qian, Gao (Frontiers in Materials, 2024)
The Jinchuan Nickel Mine is the largest large-scale copper–nickel sulfide deposit in China and the third largest in the world. Due to the deep burial of the ore body, high geostress, and broken ore rock, the downward layered cementing and filling mining method with high cost and low production capacity is adopted. The Jinchuan Nickel Mine uses bar milling sand as the filling aggregate and cement as the cementing material and adopts pipeline autoclave conveying filling mining technology with a high cement-to-sand ratio and high concentration of filling slurry, which results in the high cost of filling mining and poor mining economic benefits. In order to reduce the cost of filling mining, the Jinchuan Nickel Mine has carried out a series of research on low-cost filling mining technology by utilizing solid waste, such as using metallurgical slag instead of cement to develop low-cost filling cementitious material, using waste rock and bar mill sand as the mixed aggregate, using waste rock and tailing sand as the mixed aggregate, mixing fly ash with the mixed aggregate, and mixing copper processing tailing with the mixed aggregate. The strength of the 3d, 7d, and 28d cemented filling body of waste rock and bar mill sand reached 1.5 MPa, 2.6 MPa, and 4.8 MPa, respectively; the strength of the 3d, 7d, and 28d cemented filling body of waste rock tailings reached 4.7 MPa, 6.1 MPa, and 9.0 MPa, respectively; the strength of the 3d, 7d, and 28d cemented filling body of mixed fly ash reached 2.0 MPa, 2.0 MPa, 6.1 MPa, and 9.0 MPa, respectively; the strength of 3d, 7d, and 28d doped fly ash cemented filling body reached 2.0 MPa, 2.7 MPa, and 5.9 MPa, respectively; the strength of the 3d, 7d, and 28d doped copper-selecting tailings cemented filling body reached 1.55 MPa, 3.11 MPa, and 5.10 MPa respectively; and the strength of 3d early-strength type green filling cementitious material increased to 1.73 MPa. The application of cemented filling with solid waste resources in the Jinchuan Nickel Mine has been successful and popularized and applied in the Longshou Mine and the second mine area. Early-strength green filling cementitious materials and mixed aggregate paste filling technology are the research and development direction for utilization in Jinchuan Nickel Mine filling and mining.